Investigación en modo 3: Una alternativa para la articulación investigación e intervención en educación superior (2016)
The substantive functions of higher education: teaching, research, and social projection, require today, in ways that allow them to create links to facilitate their integration not only with disciplinary and professional fields, but also with social scenarios in order to provide responses to the demands of communities. Answering these demands requires not only of the three functions, but also thought processes of intervention. An alternative that allows joint functions, can be from link research and intervention in Mode 3 knowledge, since this allows among other things going to the place of events and knowledge, in which communities develop their capacity can lead agency and analysis processes and social transformation.